Gambaran Pengetahuan dan Sikap Ibu Tentang Pemberian Imunisasi Measles Rubella (Mr ) pada Balita di Puskesmas Tahtul Yaman Kota Jambi - Fitri Ramadani; Tuhu Perwitasari; Aryani Puspasari (Jurnal Akademika Baiturrahim Jambi, 2020)
Measles and rubella are two infectious diseases that are very contagious. Just like a disease causedby a virus in general, both of these diseases have no treatment, but can be prevented by immunization. Toddler mortality rate in the world reaches 34/1000 live births caused by various diseases that can actually be prevented by immunization. This study aimed to determine the description of knowledge and mother’s attitude  about measles rubella (MR) in toddlers at the public health center Tahtul Yaman Jambi city year 2019. This is a descriptive research. It was conducted on August 19-23 2019. Populations were all off toddler’s mother at the public health center Tahtul Yaman as many as 992. Samples were 42 respondents by using accidental sampling technique. The collecting of data used a questionnaire. It analyzed as univariate. The findings were obtained that most of respondents did not provide MR immunization for toddlers as many as 71%. Most of respondents have enough knowledge as many as 55%. Most of respondents have positive attitude as many as 60%. This study can be concluded that most of respondents did not provide MR immunization for toddlers, has sufficient knowledge and a positive attitude. Health personal at the public health center should make a schedule of counseling, information and education about MR immunization by using media that is interesting and easily understood  by the community especially toddler’s mothers. The public health center should cooperate  with the department of religion, community leaders and religious leaders to work together in synergy to disseminate information and information about the importance of MR immunization